Pengaruh Pembayaran Cash On Delivery Dan Online Customer Rating Terhadap Keputusan Pembelian Di Shoope (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan Tahun 2022) - Ahmad Miftahul Ulum; N. Rachma; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the effect of cash on delivery  payment and online customer rating on purchasing decisions on the Shopee e-commerce platform. This research employed a quantitative approach using a survey method by distributing questionnaires to 105 students of the Faculty of Economics and Business, Universitas Islam Malang, class of 2022. Data were analyzed using multiple linear regression with SPSS. The results show that simultaneously cash on delivery and online customer rating have a positive and significant effect on purchasing decisions. Partially, cash on delivery has a positive and significant effect on purchasing decisions, and online customer rating also has a positive and significant effect. These findings indicate that transaction security and social information from customer ratings are important factors in enhancing consumer purchasing decisions. Keywords: Cash On Delivery, Online Customer Rating, Purchasing Decision, Shopee